The effect of alfalfa and cornstalk round bale processing type on animal performance, wastage, preference, and mixing characteristics - Jones, Spencer Q. (Kansas State University, 2009)
Seven experiments were conducted to evaluate the effect of alfalfa and cornstalk round bale processing type on animal performance, wastage, preference, and mixing characteristics. All bales were baled using a round baler (John Deere) that had the ability to cut forage being baled prior to wrapping. This machine processed all bales used in these experiments, with those termed conventional being baled with the cutter disengaged. In Exp. 1, 46 heifers (initially 270 kg BW) were used in a 27 d experiment with ADG being higher (P < 0.01) for heifers consuming precut alfalfa compared to conventional alfalfa in ring feeders. However, there was no difference in final BW (P = 0.56) between conventional and precut treatments. In Exp. 2, 46 heifers were used to show there was no (P > 0.05) difference in forage wastage from ring feeders between precut or conventional alfalfa. In Exp. 3, 26 beef heifers, (initially 305 kg) were used to show that there was no (P = 0.48) difference in the preference of conventional alfalfa or precut alfalfa when offered simultaneously in different ring feeders for 2 d. In Exp. 4, 75 bulls (initially 317 kg BW) were used to show that tub ground bales had smaller TMR particle size (P = 0.01) than TMR’s with conventional or precut alfalfa bales. In Exp. 5, 60 heifers (initially 332 kg BW) were used to show that different discharge locations from each of the different cornstalk treatments had similar (P > 0.11) DM, CP, ADF, and NDF. Mixing time and fuel usage of a vertical mixer were evaluated in Exp. 6 and 7. In Exp. 6, bale mixing time was shorter (P < 0.05) for precut alfalfa compared to conventional alfalfa bales. Fuel usage per bale was lower (P < 0.001) for precut alfalfa bales compared to conventional alfalfa bales. In Exp. 7, precut cornstalk bale mixing time was shorter (P < 0.001) than conventional cornstalk bales. Fuel usage was similar (P > 0.05) among precut and conventionally-processed cornstalk bales. In conclusion, precutting alfalfa or cornstalk bales prior to net wrapping improved heifer performance and decreased mixing time and tractor fuel usage, but did not affect wastage and preference.
Keywords: alfalfa; cornstalk; beef; nutrition; Agriculture, Animal Culture and Nutrition (0475)